Concentração da solução nutritiva no cultivo do meloeiro em Sistema semi-hidropônico - Silva, Karen Mariany Pereira (Universidade Federal Rural do Semi-Árido, 2015)
The State of Rio Grande do Norte is the second largest exporter of melons from Brazil. It is in the region of Natal, which concentrates most of the production , the shortage of good quality water has limited the increase in irrigated area . The semi- hydroponic cultivation has become an alternative for allowing a production efficiency and ease the absorption of water and nutrients by plants. This study aimed to evaluate the growth, production and postharvest quality of melon Gaul ( Cucumis melo L. cv " NECTA " ) , grown in semi -hydroponic system. The survey was conducted in a greenhouse at the Department of Environmental Sciences and Technology of the Federal Rural University of semiarid - UFERSA , from June to August 2014. The experimental design was a randomized complete block design with five blocks and five replications , totaling 25 plants per experimental plots . We evaluated the effect of macronutrient five concentrations for the proportions of ( 12.5, 25, 50 , 75, 100%), the quantity of nutrients proposed for melon cultivation. Ten days after transplanting , the variables were analyzed : plant height ; stem diameter ; Leaf area ; number of leaves, fruit weight, transversal and longitudinal diameter , transverse and longitudinal internal cavity , thick peel and pulp , soluble solids, titratable acidity , pH, total sugars and fruit maturation relationship. Data were subjected to analysis of variance and comparison of means by Tukey test at 5 % probability. The variation of nutrient concentration influenced the behavior of the variables . The 50% concentration of nutrients provided greater weight and better fruit pulp thickness and smaller diameter stem. The concentration of 12.5 % of nutrient concentration, provided significant results for titratable acidity and soluble solids
Concentration of nutrient solution of melon growing in semi - hydroponic system
Keywords: Keywords: Cucumismelo L.; Cultivation without soil; Nutrient solution; Cucumis melo L.; Cultivo sem solo; Solução nutritiva; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO